2001
DOI: 10.1128/aac.45.3.727-733.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mutations That Confer Antibiotic Resistance in Helicobacter pylori

Abstract: In this study, we systematically examined in vitro frequencies and spectra of the spontaneous mutations in Helicobacter pylori that confer resistance to clarithromycin (Cla r Antibiotic resistance is an increasing problem for the treatment of infectious diseases. Bacteria have evolved diverse mechanisms (pathways) of resistance to antimicrobial agents, including control of uptake and efflux of drugs, modification and detoxification of drugs, alteration and protection of the target sites, and acquisition of het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 28 publications
8
117
2
Order By: Relevance
“…Wang et al reported that the L525I point mutation induced strong resistance to rifampicin. 22 In our study, the strain harboring the L525I mutation showed resistance to rifabutin. The fact that the rifabutin-resistant strain was eradicated with a 14-day regimen as a fourth-line therapy suggested that there are two possibilities for successful eradication: first, the high dose of PPI may enforce the activity of amoxicillin and rifabutin, and second, rifabutin and amoxicillin may exhibit a synergistic effect on antimicrobial activity.…”
Section: Discussionmentioning
confidence: 94%
“…Wang et al reported that the L525I point mutation induced strong resistance to rifampicin. 22 In our study, the strain harboring the L525I mutation showed resistance to rifabutin. The fact that the rifabutin-resistant strain was eradicated with a 14-day regimen as a fourth-line therapy suggested that there are two possibilities for successful eradication: first, the high dose of PPI may enforce the activity of amoxicillin and rifabutin, and second, rifabutin and amoxicillin may exhibit a synergistic effect on antimicrobial activity.…”
Section: Discussionmentioning
confidence: 94%
“…Moore et al (1995) reported four mutations of the A subunit of the DNA gyrase (GyrA) at amino acid 87 (Asn to Lys), 88 (Ala to Val), 91 (Asp to Gly, Asn or Tyr) and a double substitution at 91 and 97 (Ala to Val) in H. pylori strains with secondary resistance to ciprofloxacin. Moreover, in one in vitro study with the serial passage method, GyrA mutation at amino acid 91 (Asp to Ala, Gly, Asn or Tyr) was also reported in the ciprofloxacin-resistant strains (Wang et al, 2001). Our primary resistant strains showed three point mutations at amino acid 91 (Asp to Tyr, G271T; Asp to Asn, G271A; Asp to Gly, A272G).…”
Section: S Fujimura and Othersmentioning
confidence: 96%
“…5, 0 . 5 and 8 mg l À1 , respectively (Wang et al, 2001). H. pylori NCTC 49503 was studied as the control organism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a small number of metronidazole-resistant strains of H. pylori have been reported in which the nucleotide sequence of the rdxA gene has been unchanged there has been no further analysis of these mutants to confirm whether they have decreased RdxA activity or synthesis (1,14,31,35). We are now examining whether the RdxA enzymes produced by the two resistant strains are functionally inactive or whether other mechanisms are responsible for their resistant phenotype.…”
Section: Discussionmentioning
confidence: 99%